LED Lighting – Modification of Growth, Metabolism, Yield and Flour Composition in Wheat by Spectral Quality and Intensity - Monostori, István; Heilmann, Márk; Kocsy, Gábor; Rakszegi, Marianna; Ahres, Mohamed; Altenbach, Susan B.; Szalai, Gabriella; Pál, Magda; Toldi, Dávid; Simon-Sarkadi, Livia; Harnos, Noémi; Galiba, Gábor; et al. (Frontiers in Plant Science, 2018)
The use of light-emitting diode (LED) technology for plant cultivation under controlled environmental conditions can result in significant reductions in energy consumption. However, there is still a lack of detailed information on the lighting conditions required for optimal growth of different plant species and the effects of light intensity and spectral composition on plant metabolism and nutritional quality. In the present study, wheat plants were grown under six regimens designed to compare the effects of LED and conventional fluorescent lights on growth and development, leaf photosynthesis, thiol and amino acid metabolism as well as grain yield and flour quality of wheat. Benefits of LED light sources over fluorescent lighting were manifested in both yield and quality of wheat. Elevated light intensities made possible with LEDs increased photosynthetic activity, the number of tillers, biomass and yield. At lower light intensities, blue, green and far-red light operated antagonistically during the stem elongation period. High photosynthetic activity was achieved when at least 50% of red light was applied during cultivation. A high proportion of blue light prolonged the juvenile phase, while the shortest flowering time was achieved when the blue to red ratio was around one. Blue and far-red light affected the glutathione- and proline-dependent redox environment in leaves. LEDs, especially in Blue, Pink and Red Low Light (RedLL) regimens improved flour quality by modifying starch and protein content, dough strength and extensibility as demonstrated by the ratios of high to low molecular weight glutenins, ratios of glutenins to gliadins and gluten spread values. These results clearly show that LEDs are efficient for experimental wheat cultivation, and make it possible to optimize the growth conditions and to manipulate metabolism, yield and quality through modification of light quality and quantity.